2022
DOI: 10.3390/ph15101223
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Inhaled Ciprofloxacin-Loaded Poly(2-ethyl-2-oxazoline) Nanoparticle Dry Powder Inhaler Formulation in High Stressed Conditions

Abstract: In this study, the stability of ciprofloxacin (CIP)-loaded poly(2-ethyl-2-oxazoline) (PEtOx) nanoparticles (NPs) was investigated at normal and high stressed conditions. The blank NPs were used to understand the intrinsic physicochemical properties of the polymer NPs under these storage conditions. The formulated NPs were prepared by a coassembly reaction and dried by lyophilization. The powder NPs were stored at controlled room temperature (25 °C) with normal relative humidity (RH) (43%) and high temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Throughout the testing period, they showed no signs of aggregation. A slightly rougher surface can be observed because the humidity caused moisture absorption [ 60 ]. The results of the laser diffraction method were similar to the results of the ImageJ 1.53e software, which was utilized to determine the particle size based on the pictures ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the testing period, they showed no signs of aggregation. A slightly rougher surface can be observed because the humidity caused moisture absorption [ 60 ]. The results of the laser diffraction method were similar to the results of the ImageJ 1.53e software, which was utilized to determine the particle size based on the pictures ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the testing period, they showed no signs of aggregation. A slightly rougher surface can be observed because the humidity caused moisture absorption [60].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…The formulations were also studied to determine the drug-loading and drug-release characteristics of the PEtOx polymer. We have recently investigated the stability of the CIP-loaded PEtOx NPs DPI formulation in highly stressed conditions [43]. In this present study, the bactericidal effects of the formulated CIP-loaded PEtOx NPs were determined compared to free CIP against S. aureus and P. aeruginosa.…”
Section: Introductionmentioning
confidence: 96%
“…Studies have also confirmed the important role of sewer transmission due to fecal aerosols in community outbreaks through case-by-case analysis [27] . Since polymeric aerosols undergo a decay process differing from the general composition of pollution gases [28] , research simulated the diffusion transport process of solid-liquid droplets in an outdoor environment by CFD to demonstrate that droplet transmission of virus-carrying droplets can lead to the outdoor spread of respiratory infections [29] . Under the influence of boundary layer turbulence characteristics and meteorological processes, their concentrations of droplets exhibit complex spatial and temporal distributions.…”
Section: Introductionmentioning
confidence: 99%